Igualdad, calidad y confianza entre los desafíos de la reforma educativa francesa: la Loi n° 2019-791 du 26 juillet 2019 pour une école de la confiance - Sánchez Lissen, Encarnación; Sianes Bautista, Alicia (Revista Española de Educación Comparada, 2020)
With both the promulgation and enactment of the Loi no 2019-791 du 26 juillet 2019 pour une ecole de la confiance, a new period of normative changes has begun in France. These changes concern the organisation, structure and even certain principles the French educational system has been erected with. In the name of confidence some measures have been purposed, some of them of great magnitude, with the main purpose of guaranteeing equal opportunities for the student body of this country. In order to do that, there have been expounded, among others, initiatives focused on the extension of school attendance, diversity outreach, teacher training, institutional innovations by creating new organisms and evaluation measurements in support of educational quality. From an international and comparative perspective, the analysis of this act generates great interest, on the one hand, because of the contents it tackles and, on the other hand, because of the role France has played as a laboratory and enterprising country in educational issues throughout history. This circumstance turns it into referent of other countries in southern Europe, Africa and even Asia, which influence in their educational systems is indubitable. Without losing sight of the magnitude of this reform and its relevance, this brief analysis recognises its significance and the remarkable impact that is generating, both inside and outside of the country. Probably, from now on, there will not be just a few papers that highlight the scope of its proposals and its possible consequences.
Equality, quality and confidence among the challenges of the French Educational Reform: the Loi no 2019-791 du 26 juillet 2019 pour une ecole de la confiance
Con la promulgación y puesta en marcha de la Loi nº 2019-791 du 26 juillet 2019 pour une école de la confiance se inicia en Francia un período de cambios normativos. Éstos afectan a la organización, la estructura e incluso a determinados principios con los que se construye el sistema educativo francés. En nombre de la confianza se proponen medidas, algunas de ellas de gran envergadura, con la finalidad última de garantizar la igualdad de oportunidades para el alumnado de este país. A tal efecto se exponen, entre otras, iniciativas dirigidas a la ampliación de la escolarización, la atención a la diversidad, la formación del profesorado, innovaciones institucionales, con la creación de nuevos organismos y medidas de evaluación, en pro de la calidad educativa. Desde una perspectiva internacional y comparada, el análisis de esta ley suscita gran interés, por un lado, por el contenido que se aborda y por otro, por el papel que viene desempeñando Francia como país laboratorio, como país emprendedor en asuntos educativos a lo largo de la historia. Esta circunstancia lo convierte en referente de otros países de Europa Meridional, África e incluso Asia, cuya influencia en sus sistemas educativos resulta incuestionable. Sin perder de vista la magnitud de la reforma, de su importancia, este breve análisis conviene en reconocer la trascendencia de la misma y la notable repercusión que, tanto dentro como fuera del propio país, está provocando. Probablemente, en adelante, no pocos artículos resaltarán el alcance de sus propuestas y sus posibles consecuencias.
Keywords: act; France; confidence; education; equal opportunity; ley; Francia; confianza; educación; igualdad de oportunidades; Emerging; Scopus